A High School Kendo-team Survey of Békésy's Audiogram and EOAE - Inoue, Tsuneo; Tanaka, Yasuo; Inoue, Yoshie; Naito, Hisae; Niki, Hirofumi; Satake, Kiwamu (AUDIOLOGY JAPAN, 1995)
Twenty two members of a high school Kendoteam were examined for their hearing and evoked otoacoustic emissions (EOAE) in order to ascertain the previously-reported relationship between dip type hearing loss and continuous EOAE (C-EOAE). The measured noise level during kendo practice of kakarigeiko or a facer, “Mehn” was around 100 dBLAeq. The incidence of micro-dip positive ears in all subjects was 77.2%. The incience of C-EOAE positive ears in all subjects was 54.5%, whereas it was 67.6% in the ears with micro-dip, and 10% in the ears without. There was a significant relationship between micro-dip and C-EOAE (Q=0.90). In addition to our previous result of brass band surveys in a junior high school, the present study suggested that the C-EOAE possibly expresses a disposition of inner ear susceptibility. It was expected that EOAE measurement is useful for predicting the inner ear susceptibility to noise-induced hearing damage. Further investigation is, however, needed for verification of micro-dips as an initial sign of noiseinduced hearing damage.